Regulation of the Development of Small Business and its Social Responsibility - BONDARUKТ.; BONDARUKІ. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2019)
In the developed countries, functions of the central government policy on regulation of small business are for the most part concentrated in local administration bodies. Practices of these countries need to be considered in creating the regulatory system focused on the development of small business and its social responsibility. The theoretical principles for the process of regulation of the development of social responsibility of small business are extended. A brief review of the most widespread models for socially responsible business is made, dependent on national and cultural peculiarities. It is demonstrated that the Ukraine’s integration in the European economic area, apart from corporate social responsibility of large business, requires implementation of social responsibility of small business. It is substantiated that the regulation of the development of small business and its social responsibility, if implemented on the continuous basis, will create highly performing small business sector in Ukraine, contributing in the production output, revenue collection, and employment. A system approach to the regulation of the development of social responsibility of small business is proposed, which is based on interactions of three parties: state power bodies and local self-government bodies; the center for promotion of small business, associating small enterprises; public associations and professional unions. It is substantiated that the system approach to the regulation of the development of social responsibility of small business should be based on interactions in organizational, consultative and educational, social, financial and investment areas.